Transition Metal Carbides Filler-Reinforced Composite Polymer Electrolyte for Solid-State Lithium-Sulfur Batteries at Room Temperature: Breakthrough - Basem Al Alwan; Zhao Wang; Wissam Fawaz; K. Y. Simon Ng (Energies, 2022)
All solid-state room-temperature lithium-sulfur (Li-S) batteries have gained increasing attention due to their ability to eliminate the polysulfides shuttle effects and the safety dangers associated with the liquid electrolytes. Herein, a novel composite solid-state electrolyte, which is nickel-tungsten carbides (NiWC) over mesoporous silica (SBA-15) filled polyethylene oxide (PEO), was developed and investigated for Li-S batteries. The filler minimizes the crystallinity of the PEO and increases the ionic conductivity of the electrolyte, resulting in lowering the AC impedance of electrolyte composite from 26,256 ohm to 2416 ohm and to 5734 ohm after adding the electrolyte material with Ni/W ratios of 1:1 and 9:1, respectively. A high initial specific capacity of 1305 mAh g−1 and a capacity retention of 66.7% after 8 cycles at C/10 was obtained at room temperature after adding NiWC/SBA-15 with a Ni/W ratio of 1:1. This novel composite solid-state electrolyte shows a remarkable long-term performance at high current rates (1, 2, 4, and 5C) and rate capabilities at 0.1, 0.2, 0.5, 1, 2, 4 and back to 0.1C. The battery was able to recover 77% of the initial specific capacity at 0.1C. The materials were characterized by XRD and SEM-EDX to study the crystallinity and elemental distributions, respectively.